Elaborating Funds of Knowledge: Community-Oriented Practices in International Contexts. (November 2019) - Moll, Luis C.
This article discusses a sociocultural approach we have developed, which we refer to as funds of knowledge . The emphasis of the funds of knowledge work has been to develop both theory and methods through which educators can approach and document the funds of knowledge of families and re-present them on the bases of the knowledge, resources, and strengths they possess, thus challenging deficit orientations that are so dominant, in particular, in the education of working-class children. In this article, I present a translocation view of funds of knowledge and what we can learn theoretically and methodologically from this body of work. I review four studies conducted in different countries and sociocultural contexts. In each context, the researchers reorient the concept of funds of knowledge to address issues germane to their settings. The four studies from New Zealand, Spain, Australia, and Uganda used funds of knowledge to generate new ideas and positionalities regarding work with teachers, students, and families. None of the projects simply replicated the original studies conducted in the United States. The four studies documented empirically and represent pedagogically families and students as resourceful and helped educators arrange environments that are academically sound and strongly oriented to building on such resources for learning.